Neisseria gonorrhoeae lipooligosaccharide glycan epitopes recognized by bactericidal IgG antibodies elicited by the meningococcal group B-directed vaccine, MenB-4C - Tzeng, Yih-Ling; Sannigrahi, Soma; Borrow, Ray; Stephens, David S. (Frontiers in Immunology, 2024)
Outer membrane vesicles (OMVs) of the Neisseria meningitidis (Nm) in the group Bdirected vaccine MenB-4C (Bexsero R ) protect against infections with N. gonorrhoeae (Ng). The immunologic basis for protection remains unclear. Nm OMV vaccines generate human antibodies to Nm and Ng lipooligosaccharide (LOS/endotoxin), but the structural specificity of these LOS antibodies is not defined. Ten paired human sera obtained pre-and post-MenB-4C immunization were used in Western blots to probe Nm and Ng LOS. Post MenB-4C sera (7v5, 19v5,17v5), representing individual human variability in LOS recognition, were then used to interrogate structurally defined LOSs of Nm and Ng strains and mutants, and studied in bactericidal assays. Post MenB-4C sera recognized both Nm and Ng LOS species, ~10% of total IgG to gonococcal OMV antigens. Nm and Ng LOSs were broadly recognized by post-IgG antibodies but with individual variability for LOS structures. Deep truncation of LOS, specifically a rfaK mutant without α-, β-or γ-chain glycosylation, eliminated LOS recognition by all post-vaccine sera. Serum 7v5 IgG antibodies recognized the unsialyated L1 α-chain and a 3-PEA-HepII or 6-PEA-HepII was part of the conformational epitope. Replacing the 3-PEA on HepII with a 3-Glc blocked 7v5 IgG antibody recognition of Nm and Ng LOSs. Serum 19v5 recognized lactoneotetrose (LNT) or L1 LOS-expressing Nm or Ng with a minimal α-chain structure of Gal-Glc-HepI (L8), a 3-PEA-HepII or 6-PEA-HepII was again part of the conformational epitope and a 3-Glc-HepII blocked 19v5 antibody binding. Serum 17v5 LOS antibodies recognized LNT or L1 α-chains with a minimal HepI structure of three sugars, and no requirement for HepII modifications. These LOS antibodies contributed to serum bactericidal activity against Ng. MenB-4C vaccination elicits bactericidal IgG antibodies to Ng conformational epitopes involving HepI and HepII glycosylated LOS structures shared between Nm and Ng. LOS structure should be considered in next generation gonococcal vaccine design.